2014
DOI: 10.1093/ejcts/ezu168
|View full text |Cite
|
Sign up to set email alerts
|

Early oral feeding following thoracolaparoscopic oesophagectomy for oesophageal cancer

Abstract: Compared with preoperative gastric emptying, early postoperative gastric emptying for liquid food after oesophagectomy is significantly faster. Postoperative early oral feeding in patients with thoracolaparoscopic oesophagectomy is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
88
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 20 publications
1
88
1
4
Order By: Relevance
“…Rather, the earlier reintroduction of oral or enteral fluids was associated with a reduced length of hospital stay, with a combined mean length of hospital stay of 19±5 vs 25±18 days (mean ± standard deviation [SD]). [15][16][17] The overall complication rates were similar between the two groups (40% vs 45%). The three studies that measured duration of postoperative ileus time found that earlier reintroduction of oral or enteral intake reduced duration of ileus from a mean of 7 days (SD 2) to a mean of 5 days (SD 1).…”
Section: Early Challenges Interruption Of Oral Dietmentioning
confidence: 73%
See 2 more Smart Citations
“…Rather, the earlier reintroduction of oral or enteral fluids was associated with a reduced length of hospital stay, with a combined mean length of hospital stay of 19±5 vs 25±18 days (mean ± standard deviation [SD]). [15][16][17] The overall complication rates were similar between the two groups (40% vs 45%). The three studies that measured duration of postoperative ileus time found that earlier reintroduction of oral or enteral intake reduced duration of ileus from a mean of 7 days (SD 2) to a mean of 5 days (SD 1).…”
Section: Early Challenges Interruption Of Oral Dietmentioning
confidence: 73%
“…Table 2 summarizes the four cohort studies that evaluated optimal timing of reestablishing oral or enteral fluid intake. [15][16][17][18] The earlier reintroduction of oral or enteral fluid had no deleterious effects on clinical outcome, specifically anastomotic leak. Rather, the earlier reintroduction of oral or enteral fluids was associated with a reduced length of hospital stay, with a combined mean length of hospital stay of 19±5 vs 25±18 days (mean ± standard deviation [SD]).…”
Section: Early Challenges Interruption Of Oral Dietmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the gastric emptying for liquid food after esophagectomy was significantly faster in the early oral feeding group (1).…”
mentioning
confidence: 91%
“…Advancements in technology and techniques have affected every surgical field, and it is our hope that these further advancements should spread to other fields as well. For example, laparoscopic, urologic, cardiac, hepatobiliary, and hepatic surgical fields may also be able to reduce the use of a gastric or drainage tube to a patient's benefit (11). However, the indications and contraindications for each tube in each field still require extensive investigation.…”
mentioning
confidence: 99%